1969
DOI: 10.1128/am.17.4.596-602.1969
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microflora in Healthy Persons in a Preindustrial Region

Abstract: Procedures for quantitating the fecal microflora of man were described. Special attention was given to criteria for characterizing the culturable aerobic, Micro-aerophilic, and anaerobic bacteria. Three groups of healthy persons were studied: wholly breast—fed infants (2 to 4 month-olds), weanlings (1 to 2 year-olds), and adults. In breast-fed children, bifidobacteria predominate and outnumber by one or several logs all other culturable bacteria. The fecal flora of wholly breast-fed infants is “simpler” and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1970
1970
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Anaerobes were considered to be the major component of gut microflora [13], however this seems biased as a great majority of studies concentrated their efforts on these specific bacteria [5].I n 1969, Hungate revolutionized the anaerobic culture in developing the roll tube technique [17], thus allowing isolation of extremely oxygen-sensitive (EOS) bacteria. Several species (within genera Bacteroides, Clostridium, Veillonella, Ruminococcus, Eubacterium, Bifidobacterium, Lactobacillus, Fusobacterium, Peptococcus and Peptostreptococcus) were considered to dominate the gut microbiota.…”
Section: Culture-based Methods As the Pioneer Strategy For Human Gut Microbiota Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Anaerobes were considered to be the major component of gut microflora [13], however this seems biased as a great majority of studies concentrated their efforts on these specific bacteria [5].I n 1969, Hungate revolutionized the anaerobic culture in developing the roll tube technique [17], thus allowing isolation of extremely oxygen-sensitive (EOS) bacteria. Several species (within genera Bacteroides, Clostridium, Veillonella, Ruminococcus, Eubacterium, Bifidobacterium, Lactobacillus, Fusobacterium, Peptococcus and Peptostreptococcus) were considered to dominate the gut microbiota.…”
Section: Culture-based Methods As the Pioneer Strategy For Human Gut Microbiota Researchmentioning
confidence: 99%
“…Several species (within genera Bacteroides, Clostridium, Veillonella, Ruminococcus, Eubacterium, Bifidobacterium, Lactobacillus, Fusobacterium, Peptococcus and Peptostreptococcus) were considered to dominate the gut microbiota. Finally, before molecular tools were incorporated, it was estimated that 400e500 different species composed the gut microflora [13,18], which remained partially characterized due to the technical limitations.…”
Section: Culture-based Methods As the Pioneer Strategy For Human Gut Microbiota Researchmentioning
confidence: 99%
“…Various pathways for early patterns of microbial colonization are enumerated as follows (Millar et al , 2003):enhancement of the mucosal protective barrier;modification of systemic immune response;competitive exclusion of less desirable microbe;protein and carbohydrate degradation;vitamin and butyrate production; andmucosal differentiation.Gut flora changes with age, most markedly by a decline in bifidobacteria population (Reuter, 2001) and the intestinal microbiota consists of a complex and diverse society of both pathogenic and non‐pathogenic bacteria (Fedorak and Madsen, 2004). Mata et al (1969) detected faecal bifidobacteria population in breast‐fed infant at a level of 10 11 , which reduced to 10 10 and 10 9 cells/g, respectively during weanling and adulthood. It has been established that an “optimum balance” in microbial population in our digestive tract is associated with good nutrition and health (Rybka and Kailasapathy, 1995) and any disturbance in the balance between beneficial and potentially harmful bacteria in the intestine may pose initiation of acute or chronic diseases (Manning and Gibson, 2004).…”
Section: Microbial Colonization Of Gutmentioning
confidence: 93%
“…Guemonde et al (2006) identified Bifidobacterium catenulatum and Bifidobacterium longum as the most prevalent group of bifidobacteria, respectively after five days and three weeks of age of infants. Faecal bifidobacteria population (log cfu/ml) elevated with increasing age (ten to 40 days) of infants from 9.19-9.61 to 10.67-11.04 (Ram and Chander, 2000) but reduced to a level of 10.0 and fewer during weanling (Mata et al, 1969) and adulthood (Del Piano et al, 2004), respectively. Typical composition of intestinal flora (Table I), indicated diversity in distribution of aerobic or facultative and anaerobic bacteria in stomach, jejunum, ileum and faeces (Simon and Gorbach, 1984) and is influenced by various factors such as age, nutritional requirements, susceptible to infection, immunological status of the host and the pH, transit time, interactions between flora components, presence and availability of fermentable materials in the gut (Collins and Gibson, 1999).…”
Section: Colonization Of the Gutmentioning
confidence: 99%